DEVELOPMENT OF THE QUALITY MANAGEMENT SYSTEM IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT AND THE “GREEN ECONOMY” CONCEPT - Ibroximova Zuhra Baxtiyor qizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article highlights the issues of developing the Quality Management System within the framework of sustainable development and the “green economy” concepts. The purpose of the study is to identify directions for improving the quality management system in Uzbekistan in accordance with the principles of environmental and social sustainability. The article analyzes international experience, particularly scientific approaches to integrating quality management and “green innovations” in China, Indonesia, and European countries.